Peran Hukum Lingkungan Dalam Upaya Menjaga Sumberdaya Alam Demi Keberlangsungan Hidup Manusia - Ika Yanuar Margiyanti; Irwan Triadi (Jurnal Hukum dan Sosial Politik, 2024)
The environment is a natural resource that brings great benefits to the survival of society. Problems regarding the environment are currently quite complex problems to discuss considering that the current natural conditions are not getting better, but it can be said that the current natural conditions are getting worse. So the environment currently really needs special attention to continue to be well looked after and preserved. The research method used is normative research or library research, meaning that this research is based on library sources to discuss the problems that have been formulated. This normative research is a process of finding legal rules to answer the legal issues faced. This research uses primary legal materials as main data, secondary legal materials as supporting and complementary data, and testier legal materials as explanatory data from primary and secondary legal materials. Currently, the main spearhead of environmental problems comes from public awareness of environmental sustainability so that if a sense of awareness arises in a person it will create a feeling of protecting, preserving and utilizing the environment wisely. So regulations are needed that can regulate the environment to overcome this problem. Law Number 32 of 2009 concerning Environmental Protection and Management is expected to become a regulation that not only regulates the environment but can address various current environmental problems.